LEAPdb: a database for the late embryogenesis abundant proteins - Hunault, Gilles (BioMed Central, 2010)
BACKGROUND: Late Embryogenesis Abundant Proteins database (LEAPdb) contains resource regarding LEAP from plants and other organisms. Although LEAP are grouped into several families, there is no general consensus on their definition and on their classification. They are associated with abiotic stress tolerance, but their actual function at the molecular level is still enigmatic. The scarcity of 3-D structures for LEAP remains a handicap for their structure-function relationships analysis. Finally, the growing body of published data about LEAP represents a great amount of information that needs to be compiled, organized and classified. RESULTS: LEAPdb gathers data about 8 LEAP sub-families defined by the PFAM, the Conserved Domain and the InterPro databases. Among its functionalities, LEAPdb provides a browse interface for retrieving information on the whole database. A search interface using various criteria such as sophisticated text expression, amino acids motifs and other useful parameters allows the retrieving of refined subset of entries. LEAPdb also offers sequence similarity search. Information is displayed in re-ordering tables facilitating the analysis of data. LEAP sequences can be downloaded in three formats. Finally, the user can submit his sequence(s). LEAPdb has been conceived as a user-friendly web-based database with multiple functions to search and describe the different LEAP families. It will likely be helpful for computational analyses of their structure - function relationships. CONCLUSIONS: LEAPdb contains 769 non-redundant and curated entries, from 196 organisms. All LEAP sequences are full-length. LEAPdb is publicly available at http://forge.info.univ-angers.fr/~gh/Leadb/index.php.